Perbandingan Serat Dewarunci dan Nawarunci - Sugeng Nugroho (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2007)
This article compares between th content of Dewarunci and Nawarunci. Both tell about Bhima’s in seeking knowledge of life perfection. Serat Dewarunci which is previously believed to be created by the Moslem saints (para wali) as syncretics teachings ( a unifications of Hinde-Jawa-Islam) is most probable a composition of Nawarunci written at the end of Majapahit era.Key words: Dewarunci and Nawarunci, comaprison